The Feasibility of Indonesian Scientific-Based Learning Module with Time Token Arend Method - Nurul Komariyah; Salati Asmahasanah; Kamalludin Kamalludin (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2021)
This study aims to determine the feasibility of teaching materials in the form of scientific- based learning modules with the Arend Time token learning method, where the steps of this learning activity are designed so that students are actively involved in the learning process and carry out the social interaction process with other friends and can contribute actively. This study used Research and Development (R & D) with the Sugiyono method which consisted of 10 stages, however the researcher only used 7 stages due to the current state of Covid-19. These stages are (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) Product Revision, then followed by (7) limited production. Then the module is validated by experts consisting of design, material, and language experts using a questionnaire in the form of a validation sheet. The result of this research is that the percentage of eligibility results of design experts is 81.25% with very valid categories, 93% material experts with very valid categories, and linguists of 84.61% with very valid categories. So it can be concluded that the scientific- based Indonesian learning module with the time token method for grade IV SD / MI is feasible to use to make students actively involved in the process of learning activities.